2016
DOI: 10.1039/c5np00096c
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic approaches towards alkaloids bearing α-tertiary amines

Abstract: Alkaloids account for some of the most beautiful and biologically active natural products. Although they are usually classified along biosynthetic criteria, they can also be categorized according to certain structural motifs. Amongst these, the α-tertiary amine (ATA), i.e. a tetrasubstituted carbon atom surrounded by three carbons and one nitrogen, is particularly interesting. A limited number of methods have been described to access this functional group and fewer still are commonly used in synthesis. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
123
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 394 publications
(497 reference statements)
1
123
0
1
Order By: Relevance
“…1). However, compounds containing α-tertiary amines are typically challenging to synthesise2, and the use of unactivated ketones in the Pictet–Spengler reaction has been limited by their low reactivity and steric bulk.…”
mentioning
confidence: 99%
“…1). However, compounds containing α-tertiary amines are typically challenging to synthesise2, and the use of unactivated ketones in the Pictet–Spengler reaction has been limited by their low reactivity and steric bulk.…”
mentioning
confidence: 99%
“…Extensive investigation by Bower and co‐workers demonstrated that, by tuning the nature of the ligand and the substrate structure, it is possible to generate dihydropyrroles/perhydroindoles with concurrent generation of a secondary or tertiary stereogenic center . This is of particular importance in view of the widespread presence of chiral‐nitrogen‐containing heterocycles in natural products and drugs . Very recently, Bower and co‐workers developed the first efficient catalytic asymmetric Narasaka–Heck reaction to give 2,5,5‐trisubstituted dihydropyrroles with good to excellent enantioselectivity (Scheme b) …”
Section: Methodsmentioning
confidence: 99%
“…Theoxidative directing group [7] used herein plays several important roles,acting both as an internal oxidant and as an intramolecular nucleophile after the OÀNb ond cleavage.S ignificantly,t he present methodology affords ah ighly efficient way to construct the rearranged products [8] under mild reaction conditions with ahigh efficiency. Theoxidative directing group [7] used herein plays several important roles,acting both as an internal oxidant and as an intramolecular nucleophile after the OÀNb ond cleavage.S ignificantly,t he present methodology affords ah ighly efficient way to construct the rearranged products [8] under mild reaction conditions with ahigh efficiency.…”
mentioning
confidence: 87%
“…Described herein is the successful coupling of N-phenoxyacetamide and 7-azabenzonorbornadiene for the efficient synthesis of bridged polycyclicm olecules,w hich combines C À Ha ctivation and Wagner-Meerwein-type rearrangement using aCp*Rh III catalyst (Scheme 2). Theoxidative directing group [7] used herein plays several important roles,acting both as an internal oxidant and as an intramolecular nucleophile after the OÀNb ond cleavage.S ignificantly,t he present methodology affords ah ighly efficient way to construct the rearranged products [8] under mild reaction conditions with ahigh efficiency.…”
mentioning
confidence: 87%